ANALISIS FUNDAMENTAL SAHAM PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK (SIDO) - Keti Purnamasari; Gusti Ayu Oka Windarti; Elisa Elisa (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2022)
Fundamental analysis is carried out through the Top Down Analysis approach. This analysis is carried out sequentially starting from assessing the overall state of the economy, industry strength and company performance. Macroeconomic analysis is carried out by assessing the overall economic condition of a country such as GDP, interest rates, and exchange rates. Industry analysis assesses potential developments in industries related to companies, while company analysis uses financial ratio analysis which includes liquidity ratios, activity ratios, profitability ratios, solvency ratios, and market value. Macroeconomic analysis shows that there is an increase in GDP growth, a decrease in the BI-rate, and a depreciating rupiah exchange rate. The pharmaceutical industry in Indonesia has great opportunities when it comes to Indonesia's demographic conditions. Assessment of the company's financial performance results that the liquidity ratio has a value above the standard, which means the company has sufficient current assets to pay off its short-term obligations. The activity ratio based on the calculation results has a low inventory turnover. The profitability ratio has an increasing value which means the company is able to manage assets properly to earn a profit. The solvency ratio shows that the company is able to pay its long-term debt. Overall, in terms of market value, some ratios are good, but there is a decrease in dividend payments when viewed from dividend per share. However, this decline is not always bad because from the company's management point of view, a growing company will hold its profits to support future growth. The company reinvests its profits into the company so that the share price increases.